Sebuah Pandangan Kafir dalam Konsep Jihad - Octaviani P, Evita Dwi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2020)
Jihad is fighting earnestly according to Islamic law, jihad is carried out to carry out the main mission of mankind which is to uphold the religion of God. However, it turns out there are still many people who are mistaken in understanding this jihad case, and place it not in its proper place. The meaning of jihad becomes reduced so narrowly, as if jihad is only a matter of war and military invasion. Even though the position of qital in jihad is very great, jihad is not only about qital (war). Jihad law according to the majority of fiqh scholars argues that jihad law is fardu kifayah, although there are some of them who argue fard ‘ain. Jihad which is understood as war is divided into two parts, namely the resistance jihad and the attack jihad. Infidels who must be protected are dhimmi and infidels who must be fought are harbi infidels. There are several acts of terrorism to carry out terrorism including bombings that occurred in New York and Bali. War in Islam has an ultimate purpose. War in Islam carries the mission of truth, humanity and human dignity. And the purpose of the Islamic struggle is not for the personal interests of the fighters, not even for the interests of the Muslims, but for the benefit of humanity on earth.